The making of a quality neighbourhood park: a path model approach - Abdul Malek, Nurhayati; Mariapan, Manohar; Mohd Shariff, Mustafa Kamal (2009)
Since the Nineteenth Century, the provision of parks has been a major focus in promoting places for relaxation and recreation. In other words, parks were designed to promote public health and to give some aesthetic value to an urban setting. Neighbourhood Parks (NP) therefore can be regarded as public spaces, which cater to the needs of urban dwellers and the community as a whole. The fundamental focus of this study is to gain an increasing understanding on how park users in Malaysia interpret their leisure or recreational outdoor activities in residential green open space area. This paper explores and expended on the dimension of external and internal factors that contribute to the success of a park, in this case, we named it the ‘Quality Neighbourhood Park’ Criteria (QNPC). Attributes or construct from past literature findings in the area of use pattern, needs and preferences study towards residential open spaces area or the NP will further be tested to validate the model fits using Structural Equation Modeling (SEM) Technique. SEM statistically tests a hypothesized model to determine the consistency of that model with the sample data. The fitness of the model should help to determine and developed the intended quality criteria. This paper offers knowledge contribution to the body of literature in developing what most scholars have identified as important for future research in the field of Landscape Architecture as well as Park and Recreation Management with the integration of SEM techniques. This paper should help develop, demonstrate and validate a new approach to achieve QNPC.